PENGARUH PENDIDIKAN, PELATIHAN DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA OS HOTEL DI KOTA BATAM - M. Syarif Hidayatullah; Hikmah Hikmah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of education, training and incentives on employee performance at OS Hotel in Batam. This type of research is quantitative with a population of 101 people. The data was collected using a questionnaire and the researcher set a sample using a saturated sample. The data was processed using SPSS 26 with educational results t count > t table of 5.446 > 1.98472 with a significance value of 0.000 < 0.05 which means that education has a positive and significant effect on employee performance, t count training > t table of 5.239 > 1.98472 with a significance of 0.000 <0.05, which means that training has a positive and significant effect on employee performance. The results of the incentive t count> t table of 3.370> 1.98472 with a significance of 0.001 <0.05, which means that incentives have a positive and significant effect on employee performance. And education, training and incentives together have a positive and significant effect on employee performance as evidenced by the results of the F test with an Fcount of 96.126> Ftable 2.69 with a significance of 0.000 <0.05 and an R Square value of 0.741